2022
DOI: 10.1186/s13287-022-03037-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-17-5p from adipose-derived mesenchymal stem cells inhibits abdominal aortic aneurysm by suppressing TXNIP-NLRP3 inflammasome

Abstract: Background Preclinical studies have suggested that adipose-derived mesenchymal stem cells (ADSCs) transplantation can suppress abdominal aortic inflammation and aneurysm expansion through paracrine factors. Yet, the mechanism of action is not fully understood. In the present study, we further examined the function and mechanism of ADSC-derived exosomes (ADSC-exos) and their microRNA-17-5p (miR-17-5p) on the abdominal aortic aneurysm (AAA) progression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 48 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…Furthermore, inflammation has been demonstrated to play vital role in AAA pathology. Our previous study confirmed that inactivate TXNIP-NLRP3 inflammasome of macrophages helped inhibit the chronic inflammation of aorta thus decreasing the incidence of AAA ( 5 ). In addition, one of the key mechanisms is vascular smooth muscle cell (VSMC) apoptosis, which is considered as the critical pathogenesis of the weakness of aorta wall ( 6 , 7 ).…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…Furthermore, inflammation has been demonstrated to play vital role in AAA pathology. Our previous study confirmed that inactivate TXNIP-NLRP3 inflammasome of macrophages helped inhibit the chronic inflammation of aorta thus decreasing the incidence of AAA ( 5 ). In addition, one of the key mechanisms is vascular smooth muscle cell (VSMC) apoptosis, which is considered as the critical pathogenesis of the weakness of aorta wall ( 6 , 7 ).…”
Section: Introductionsupporting
confidence: 63%
“…In this study, we found that CRGs were correlated with inflammatory response and oxidative response, including NLRP3 and FDX1. In our previous study, macrophage NLRP3 inflammasome plays a significant role in promoting the progress of AAA (5). Furthermore, NLRP3 inflammasome activation regulates vascular smooth muscle cells phenotypic switch (49), which ultimately leads to AAA development through tunica medium elastin degradation (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations